The Influence of Region on Reading Habits in Indonesia: RM-MANOVA Analysis of Population Aged 5+ (2018) - Febyanti, Iin; Safira Devi, Arsita; Nugraheni, Setiawati; Wardah, Salsabila; Nasrudin, Muhammad; Trimono, Trimono (Parameter: Jurnal Matematika, Statistika dan Terapannya, 2025)
This study explores the reading habits of the Indonesian population aged 5 and above, focusing on differences between urban and rural areas. Using data from the 2018 BPS survey, the research examines the proportion of individuals who engaged in reading various materials in printed and electronic formats over the past seven days. A Repeated Measures Multivariate Analysis of Variance (RM MANOVA) was employed to assess the influence of regional factors on reading behavior. The results indicated significant disparities: urban populations tend to read a broader range of materials such as newspapers, magazines, and scientific texts, while rural populations focused more on textbooks and basic materials. These findings highlight the need for regionally tailored literacy strategies to ensure equitable access to reading resources across Indonesia.